2006
DOI: 10.1074/jbc.m602372200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity Profiling of Seven Human Tissue Kallikreins Reveals Individual Subsite Preferences

Abstract: Human tissue kallikreins (hKs) form a family of 15 closely related (chymo)trypsin-like serine proteinases. These tissue kallikreins are expressed in a wide range of tissues including the central nervous system, the salivary gland, and endocrine-regulated tissues, such as prostate, breast, or testis, and may have diverse physiological functions. For several tissue kallikreins, a clear correlation has been established between expression and different types of cancer. For example, the prostate-specific antigen (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
122
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(139 citation statements)
references
References 76 publications
15
122
1
1
Order By: Relevance
“…2 and 3 are consistent with the concept that coagulation proteases prefer a nonpolar residue at P2Ј position in their substrates/inhibitors (6,17,23,42). In this context, KD1-L17R has no inhibitory activity toward pKLK, FXIa, and FVIIa/sTF.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…2 and 3 are consistent with the concept that coagulation proteases prefer a nonpolar residue at P2Ј position in their substrates/inhibitors (6,17,23,42). In this context, KD1-L17R has no inhibitory activity toward pKLK, FXIa, and FVIIa/sTF.…”
Section: Discussionsupporting
confidence: 70%
“…Serine proteases are ubiquitous in living organisms and are involved in many physiologic processes, including digestion and respiration (1)(2)(3), blood coagulation and fibrinolysis (4,5), kinin formation and tumorigenesis (6), complement activation and phagocytosis (7), osteoarthritis and bone remodeling (8,9), as well as in ovogenesis and fertilization (10). Biologic activity of serine proteases is tightly regulated by their cognate inhibitors.…”
mentioning
confidence: 99%
“…non-P1 site) hydrolyses after Ala (pro-KLK9), Ser (pro-KLK13), and Leu (pro-KLK15) residues. These results show that KLK11 is capable of dual substrate specificity (both trypsinlike and chymotrypsin-like) and is in good agreement with the P1 specificity of KLK11 as determined using a positional scanning combinatorial library of tetrapeptides (52). The dual substrate specificity of KLK11 is similar to KLK1, but KLK11 exhibits a much broader specificity in contrast to KLK1.…”
Section: Discussionsupporting
confidence: 70%
“…Characterization of the potential autolytic and cross-activation potential among the members of the KLK family, and the elucidation of activation cascades regulating function, has been a subject of intense investigation (Lovgren et al 1997;Denmeade et al 2001;Takayama et al 2001a;Brattsand et al 2005;Debela et al 2006;Michael et al 2006;Memari et al 2007;Yoon et al 2007;Emami and Diamandis 2008). These studies have demonstrated the potential for complex regulatory activation cascades between members of the KLK family; however, almost nothing is known regarding the intersection of the KLK axis with other protease families.…”
Section: Discussionmentioning
confidence: 99%